The Influence of Local Revenue and Equalization Fund on Economic Growth in East Nusa Tenggara Province - Safira Dini Aini; Endah Kurnia; Sunlip Wibisono (Jurnal Ekonomi Pembangunan, 2019)
Fiscal decentralization is a policy made by the government to reduce fiscal dependence on the central government and create financial independence in the region. The independence of regional finance itself can be reflected through the high percentage of PAD revenue to total regional revenues. Where the existence of regional financial independence is expected to help implement regional development that can affect economic growth in the region. The purpose of this study was to determine the relationship of the level of regional financial independence to economic growth of districts/cities in East Nusa Tenggara Province in 2012-2017. The results of study uses secondary data analysis tools to approach the data panel Fixed Effect Model (FEM). The results of this study indicate that the local revenue had significant positive effect on economic growth, equalization funds had no significant positive effect on economic growth.